Utility of (2,4-dioxo-1,4-dihydro-2H-quinazolin-3-yl)-acetic acid hydrazide in the synthesis of some heterocyclic nitrogen compounds - Hassan, Mamdouh Adly; Seleem, Maghrabi Ali; Younes, Ahmed Mohamed Mosallem; Taha, Mohamed Mobark; Abdel-Monsef, Abou-Bakr Haredi (European Journal of Chemistry, 2013)
An efficient synthesis of (2,4-dioxo-1,4-dihydro-2H-quinazolin-3-yl)-acetic acid hydrazide (3) has been achieved and described. The obtained hydrazide (3) was used in building of some interesting heterocycles such as, triazole, oxadiazole, pyrazole, phthalazine, and indol-2-one rings at position 3. The structures of the obtained compounds were confirmed by IR, 1H NMR, 13C NMR, MS spectral and elemental analysis.